2012
DOI: 10.1093/jac/dkr576
|View full text |Cite
|
Sign up to set email alerts
|

Clonal diversity and biofilm-forming ability of methicillin-resistant Staphylococcus pseudintermedius

Abstract: A heterogeneous clonal distribution was observed among MRSP from dogs in Norway. As opposed to previous findings in Europe, MRSP clones other than ST71 have spread in Norway, such as MRSP ST106. The results also show that MRSP ST71 is possibly a good biofilm producer, and this may in turn be a contributing factor to the nosocomial character of MRSP ST71.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
62
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 38 publications
6
62
0
2
Order By: Relevance
“…For methicillin-resistant Staphylococcus aureus (MRSA), it has been shown that differential gene expression was important in the evolution of MRSA ST8 virulence and spread in the community (31). To date, the molecular determinants underlying the success of CC71 and CC258 are unknown, although Osland et al suggested that ST71 strains were better adapted to produce biofilms (32). However, the flexible availability of antimicrobial resistance genes in MRSP may, as it has been suggested before, be a strong selection factor for the dissemination of major clonal lineages (7).…”
Section: Discussionmentioning
confidence: 99%
“…For methicillin-resistant Staphylococcus aureus (MRSA), it has been shown that differential gene expression was important in the evolution of MRSA ST8 virulence and spread in the community (31). To date, the molecular determinants underlying the success of CC71 and CC258 are unknown, although Osland et al suggested that ST71 strains were better adapted to produce biofilms (32). However, the flexible availability of antimicrobial resistance genes in MRSP may, as it has been suggested before, be a strong selection factor for the dissemination of major clonal lineages (7).…”
Section: Discussionmentioning
confidence: 99%
“…The frequent carriage of prophages in the MRSP sequence type 71 (ST71) and ST68 genomes suggested they have a role in the fitness of MRSP and that the predominant transfer of genetic material in these isolates is through bacteriophage transduction, rather than plasmid conjugation, as happens in methicillin-resistant Staphylococcus aureus (MRSA) (1). MRSP isolates are able to produce biofilm, and MRSP ST71 isolates, in particular, are better biofilm producers than other MRSP clones (5,6). The icaA gene can be significantly upregulated in biofilm samples, suggesting a role in the biofilm production by S. pseudintermedius (7).…”
Section: Ethicillin-resistant Staphylococcus Pseudintermedius (Mrsp)mentioning
confidence: 99%
“…The icaA gene can be significantly upregulated in biofilm samples, suggesting a role in the biofilm production by S. pseudintermedius (7). The ability to form biofilm may play an important role in the pathophysiology of bacterial infections and can be related to survival and persistence of S. pseudintermedius, namely, MRSP, in the environment (5,6). The MRSP ST71 isolates also show greater adherence to corneocytes than MRSP non-ST71 and methicillinsusceptible S. pseudintermedius (MSSP) isolates, and thus it has been suggested that the enhanced adherence of ST71 might be a factor contributing to the epidemiological success of this MRSP lineage (2).…”
Section: Ethicillin-resistant Staphylococcus Pseudintermedius (Mrsp)mentioning
confidence: 99%
“…They also occasionally cause severe infections in humans (16,17). While one predominant MRSP clone belonging to sequence type ST71 has spread worldwide (18,19), other clonal lineages have been reported to be predominant in some countries (20,21). MRSP strains are particularly resistant to many different classes of antibiotics, such as ␤-lactams, aminoglycosides, fluoroquinolones, tetracyclines, lincosamides, macrolides, folate pathway inhibitors, and phenicols, thus limiting the therapeutic options (22,23).…”
mentioning
confidence: 99%